Inside Cover: Gift from Nature: Cyclomarin A Kills Mycobacteria and Malaria Parasites by Distinct Modes of Action (ChemBioChem 17/2015). Issue 17 (November 2015) - Bürstner, Nathalie; Roggo, Silvio; Ostermann, Nils; Blank, Jutta; Delmas, Cecile; Freuler, Felix; Gerhartz, Bernd; Hinniger, Alexandra; Hoepfner, Dominic; Liechty, Brigitta; Mihalic, Manuel; Murphy, Jason; et al.
Abstract : The inside cover picture shows the malaria parasite Plasmodium falciparum at the late schizont stage in a red blood cell. It is filled with invasive merozoites. The natural product cyclomarin A is a potent inhibitor of the growth of P. falciparum . It binds to the plasmodial enzyme diadenosine triphosphate (Ap3A) hydrolase—but not to the closest human homologue—and prevents the formation of an enzyme⋅ substrate complex. Our results validate the hydrolase as a new drug target for the treatment of malaria. More details can be found in the Communication by E. K. Schmitt et al. onpage 2433 in Issue 17, 2015 (DOI:10.1002/cbic.201500472 ).